2009
DOI: 10.1002/esp.1904
|View full text |Cite
|
Sign up to set email alerts
|

Complex relationships between salt type and rock properties in a durability experiment of multiple salt–rock treatments

Abstract: A laboratory salt weathering experiment was performed using fi ve salts to attack eight types of rocks to determine the relative signifi cance of rock durability and salt aggressivity to salt crystallization damage. The infl uence of individual rock properties on the salt susceptibility of the rocks was also evaluated. To study the relation between pore characteristics, salt uptake, and damage, the pre-and post-experiment pore size distributions of the rocks were also examined. It is observed that both salt ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…field‐exposed) concrete may therefore be indicative of an increased frequency of salt crystallization in this material type (e.g. Yu and Oguchi, ; Liu et al , ). In contrast, the retention of moisture and buffering of thermal extremes through bioerosion may reduce the efficiency of salt weathering in limestone compared to uncolonized rock (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…field‐exposed) concrete may therefore be indicative of an increased frequency of salt crystallization in this material type (e.g. Yu and Oguchi, ; Liu et al , ). In contrast, the retention of moisture and buffering of thermal extremes through bioerosion may reduce the efficiency of salt weathering in limestone compared to uncolonized rock (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Even more remarkably, Yu and Oguchi (2009) found that the relative resistance of a range of rock types to salt weathering was variable, and that the ranking of durability varied with the type of salt employed.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…究がなされてきた (Matsukura and Matsuoka, 1996; Goudie and Viles, 1997) 。松倉 2008 (Gauri, 1990;Winkler, 1994;朽津, 1994;Kuchitsu et al, 1999 (Matsukura and Matsuoka, 1996;Goudie and Viles, 1997;山田ほか, 2005;Osawa and Oguchi, 2009; Swe Yu and Oguchi, 2009 (Matsukura and Matsuoka, 1996) 指摘されている (Matsukura et al, 2004;松倉, 2008) 。また,湿度については,大気の相対湿度…”
Section: 岩盤あるいは岩石における風化作用のひとつで ある塩類風化に関して,これまでにも盛んに研unclassified